The Effectiveness of Leadership Role on Improving Work Discipline in Health Center Employee - Ratna Yuni Handayani; Suhadi Prayitno (Sarana Ilmu Indonesia (salnesia), 2022)
Leadership was the most crucial factor that influenced the organization's success in fulfilling its role to enhance employee motivation and improve work discipline. Based on the preliminary survey conducted at Tawangrejo Health Center, it was found that some employees were dissatisfied with the leadership of the head of the health center. Furthermore, it was revealed that employee work discipline, as indicated by attendance records, experienced a decline in 2018. This study aimed to determine the relationship between the role of leadership and employee work discipline at Tawangrejo Health Center in Madiun City in 2022. A quantitative approach with Kendall's Tau-b analysis was utilized in this research. The research population consisted of 73 employees, and a sample size of 42 employees was selected through simple random sampling. The analysis of this study revealed that the p-value = 0,000 (p-value< 0,05), indicating a partial relationship between the role of leadership and employee work discipline.